KEKUATAN GESER TANAH PADA BERBAGAI DOSIS PUPUK ORGANIK GRANUL - Gatot Pramuhadi; Dymaz Gonggo Yuda Arditha (JURNAL AGROTEKNOLOGI, 2011)
Plants can grow and reach maximum production on optimum soil condition. Plants growth and agricultural machines application in farm fields were influenced by physical, chemical, and mechanical properties of soil. Granule organic fertilizer (GOF) application with a certain dosage could influence physical, chemical, and mechanical properties of soil. The objective of the research was to analyse interaction relationship between physical and mechanical soil properties alterations on GOF dosages variation. Soil consistency test, compaction test (Proctor’s test), and direct shear test were applied to soil samples on GOF dosages variation. Research results showed that the increasing of GOF dosages from 0 ton/ha up to 90 tons/ha would increase soil posity of (49.43-55.85)%, soil moisture content of (24.14-49.97)%, plastic limit of (35.96-41.82)%, and liquid limit of (56.01-61.75)%, but it would decrease maximum soil dry bulk density of (1.34-1.17) g/cc. Soil shear strength decreased from (0.91-1.41) kgf/cm2 down to (0.42-0.58) kgf/cm2 by the decreasing of soil dry bulk density of (1.14-1.09) g/cc and soil cohesion of (0.68-0.34) kgf/cm2 which resulted by the increasing of the GOF dosages.Keywords: soil shear strength, granule organic fertilizer, soil density, and soil cohesion